KARAKTERISTIK BIODEGRADASI ALKIL SULFONAT LINEAR OLEH Pseudomonas aeruginosa - I Made Sudiana (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2003)
Detergent contained of Linear Alkyl Sulfonate (LAS) is toxic material to human, animal and microorganism. Strain S1 isolated from detergent contaminated soil was able to grow in media with LAS as a sole carbon source. LAS degradation took place under aerobic condition, with μmax of 0.31-h, Ks = 7.75 mg/L, Vmax = 1.04 mg/L.hour-1and Km = 8.119 mg/L. Analyses of 16s rDNA revealed that S1 is belonging to Pseudomonas aeruginosa.